Teachers' Strategies in Implementing Social Emotional Learning to Improve Student's Wellbeing - Oktriani, Neneng; Andaryani, Eka Titi; Sumartiningsih, Sri; Yuwono, Agus (Journal of English Language and Education, 2025)
A holistic education demands attention not only to the academic aspect, but also to the emotional and social development of students. Social Emotional Learning (SEL) is a strategic approach that has been proven to support the overall well-being of students. This study aims to analyze the strategies used by teachers in implementing SEL to improve students' wellbeing. The method used is qualitative descriptive with a literature study approach, which involves the analysis of fifteen articles from national and international journals published from 2020 to 2025. Data were collected through documentation and analyzed thematically to identify patterns of SEL implementation strategies by teachers and their relationship with the dimension of student welfare. The results of the study showed five main categories of strategies: integration of SEL values in the curriculum, reflective learning practices, creation of an empathetic classroom environment, provision of counseling guidance services, and teacher professional competency training. These five strategies contribute to strengthening emotional regulation, social relationships, confidence, and student learning motivation. This study concludes that effective SEL implementation requires strong teacher competence, a supportive school culture, and consistent implementation at all levels of education.